IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING AND TAHFIDZUL QURAN IN SHAPING THE CHARACTER OF MAHASANTRIWATI IN MAHAD TAHFIDZ VOCATIONAL LAYAR DAKWAH - Astarani, Thea Fitri (Universitas Dharmawangsa, 2022)
This study aims to find out: (1) Learning Islamic Religious Education and Tahfidzul Quran in shaping the character of students in Mahad Tahfidz Vocational Layar Da'wah, (2) Supporting and inhibiting factors in shaping the character of students in Ma'had Tahfidz Vocational Layar Da'wah. This study uses a qualitative method with a descriptive approach. The data of this study was obtained using observation, interview and documentation methods. These three methods are data collection techniques that will be findings in the research that can be concluded that: (1) The teaching of Islamic Religious Education and Tahfidzul Quran can help the character of students achieve their vision and mission, namely as da'i, ro'i and murobbi. (2) Supporting factors are the management of the leadership of the ma'had institution with integrity, capable teachers and educators, complete and quality learning resources, supporting facilities, and a safe and comfortable location. (3) The obstacles obtained are the lack of administrative personnel, the lack of donors for ma'had financing, and the Education Development Contribution Fee (SPP) is still quite low given by students.